THE EFFICIENCY ANALYSIS OF THE SCHEDULING ALGORITHMS OF FRAME TRANSMISSION OVER LTE NETWORK - Kolyadenko, Y. Y.; Alali, A. M. (Radio Electronics, Computer Science, Control, 2015)
The article investigates the scheduling algorithms, which are part of the subsystem to ensure quality of service in networks of LTE. The effectiveness of frame scheduling methods FIFO, SJF and RR is studied. The comparison was made by parameters such as the average waiting time, average time of packet processing, filling the buffer data and the number of dropped packets. The analysis showed that at small packet length is the average waiting time in the queue for algorithms RR and FIFO is approximately the same, and SJF algorithm efficiency by a third superior than algorithms RR and FIFO. With the increase in the average length of the packet the waiting time in the queue is growing faster for algorithm RR. The increase of waiting time in the queue for the algorithm FIFO is slightly less. The SJF algorithm has a most minimal growth of time waiting in queue. The dependences average processing time of the maximum length of packets from packets are founded. Analysis showed that algorithm SJF by this indicator gives a noticeable gain. An experiment with limited buffer queue is conducted. Analysis showed that the filling of the data buffer by FIFO algorithm is more intense than by the algorithm SJF. According to the percentage of dropped packets the SJF algorithm has the best performance. Thus, to further improve the quality and efficiency of data transmission in LTE we recommend the algorithm SJF, which gives a gain of 18% to 50%.